2004
DOI: 10.1001/archotol.130.10.1205
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Serum Soluble Intercellular Adhesion Molecule 1 and Transforming Growth Factor α in Patients With Nasopharyngeal Carcinoma

Abstract: To determine serum levels of soluble intercellular adhesion molecule 1 (sICAM-1) and transforming growth factor ␣ (TGF-␣) in 51 patients with nasopharyngeal carcinoma before, during, and after radiation therapy (5-year follow-up period). Results: The mean±SD serum levels of the 2 cytokines were found to be higher in patients before radiotherapy (sI-CAM-1, 369.6±123.7 ng/mL; TGF-␣, 36.6±24.6 ng/mL) than after radiotherapy (sICAM-1, 225.9±124.3 ng/mL; TGF-␣, 20.2±22.3 ng/mL) (PϽ.05), and they were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…ICAM‐1 is a member of immunoglobin superfamily of adhesion molecules. Both tissue ICAM‐1 and serum sICAM‐1 are commonly found in NPC biopsies, transplanted NPCs, EBV positive NPC cells and NPC patient sera in a significantly high level . In fact, our data showed consistency to this observation indicating that ICAM‐1 could be secreted from NPC cells through exosomes, subsequently, that would be transferred to other cells.…”
Section: Discussionsupporting
confidence: 84%
“…ICAM‐1 is a member of immunoglobin superfamily of adhesion molecules. Both tissue ICAM‐1 and serum sICAM‐1 are commonly found in NPC biopsies, transplanted NPCs, EBV positive NPC cells and NPC patient sera in a significantly high level . In fact, our data showed consistency to this observation indicating that ICAM‐1 could be secreted from NPC cells through exosomes, subsequently, that would be transferred to other cells.…”
Section: Discussionsupporting
confidence: 84%
“…To further support the notion that huMETCAM/MUC18 was expressed at a low level in NPC tissues, we showed that low levels of huMETCAM/ MUC18 were also expressed in seven established NPC cell lines in comparison with that in a human malignant melanoma cell line, SK-Mel-28, two metastatic human prostate cancer cell lines, DU145 and PC-3, and a human bladder cancer cell line, TSU-Pr1. Taken together, we concluded that the diminishing or the loss of huMETCAM/ MUC18 expression may be a new potential biomarker for emergence of NPC, whereas the re-gain of its expression may be a new potential biomarker for the progression of NPC to malignant stages, in addition to other potential markers for this cancer, such as the loss of E-cadherin and connexin 43 expression (Huang et al, 2001;Li et al, 2004;Yi et al, 2006), the gain of ICAM expression (Yu et al, 2004), and the presence of EBV-specific LMP1 (Tsai et al, 2002;Yoshizaki, 2002).…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, these etiological factors may induce aberrant expression of cell adhesion molecules (CAMs) in NPC, since CAMs govern the social behaviors of cells and altered expression of CAMs affects the motility and invasiveness of many tumor cells in vitro and metastasis in vivo (Cavallaro et al, 2004). For examples, up-regulation of ICAM (Yu et al, 2004) and down-regulation of E-cadherin (Huang et al, 2001;Li et al, 2004) and connexin 43 (Yi et al, 2006) correlates with the progression of NPC; however, the expression of CD44 does not (Huang et al, 2001). …”
mentioning
confidence: 99%
“…Conversely, expression differences noted in the later stages only (St4, St5, papilloma and carcinoma), are likely to result from the consequences of the earlier altered expression programmes, such as the infiltration of inflammatory cells, and act to compound the phenotype. We previously found that TGFα and other epidermal growth factor (EGFR) ligands (including HB-EGF and EPR) were consistently upregulated in the transgenic tissue from the earliest stages, indicating that induction of these ligands result directly from LMP1 expression [20,21], furthermore increased serum TGFα has been correlated with poor prognosis in NPC patients [34]. EGFR is a known target of LMP1 through NF-κB activation [35,36] and we found that EGFR was induced (and NF-κB activated) by LMP1 in the transgenic tissue, but subject to homeostatic modulation in vivo , mediated in part through TGFα [21].…”
Section: Discussionmentioning
confidence: 99%